2020
DOI: 10.1002/ejhf.1643
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function in heart failure with preserved ejection fraction: a systematic review and meta‐analysis

Abstract: Aims Left atrial (LA) mechanical function may play a significant role in the development and progression of heart failure with preserved ejection fraction (HFpEF). We performed a systematic review and meta‐analysis to evaluate association of impaired LA function with outcomes in HFpEF. Methods and results Multiple databases were searched for original studies measuring different phases of LA function in HFpEF patients. Comparative LA function between HFpEF patients and healthy controls was assessed by pooling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
93
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 49 publications
1
93
2
5
Order By: Relevance
“…Left atrial (LA) function is associated with an increased risk of HF in patients with atrial fibrillation (AF). 7 Khan et al 8 HFpEF patients compared to controls. Decreased LA reservoir strain was associated with more clinical events.…”
Section: Left Atrial Functionmentioning
confidence: 99%
“…Left atrial (LA) function is associated with an increased risk of HF in patients with atrial fibrillation (AF). 7 Khan et al 8 HFpEF patients compared to controls. Decreased LA reservoir strain was associated with more clinical events.…”
Section: Left Atrial Functionmentioning
confidence: 99%
“…LA functional parameters were pooled using weighted mean differences across studies in a random effects model, and then linked to mortality and HF hospitalization when available. 10 The authors identified 22 studies fitting the inclusion criteria, of which 16 included a control group. 10 The final pooled data included 1974 HFpEF patients and 751 controls.…”
mentioning
confidence: 99%
“…10 The authors identified 22 studies fitting the inclusion criteria, of which 16 included a control group. 10 The final pooled data included 1974 HFpEF patients and 751 controls. Almost all studies used echocardiography for LA function assessment, with only three using magnetic resonance imaging.…”
mentioning
confidence: 99%
See 2 more Smart Citations